The role of the archives in the understanding of the eviction of Alioune Diop from the Second World Black and African Festival of Arts and Culture (FESTAC 77) and its consequences - (:unkn) unknown (My University, 2023)
The eviction of Alioune Diop from the Second World Black and African Festival of Arts and Culture (FESTAC), which constitutes one of the most important events of that festival, is only understandable by extending its context beyond Nigeria. To that extent, one needs to broaden the scope of the archival research. This is how the importance of the archives of UNESCO and Présence Africaine is revealed and that the eviction of Alioune Diop appears first as an independent event of FESTAC, with has its own consequences on the historical point of view.
Keywords: African Research